An investigation on carrier transport behavior of tetragonal halide perovskite: First-principles calculation. (1st November 2022) - Su, Ye; Wang, Hao; Shi, Li-Bin; Wang, Yan-Zhou; Liu, Qing; Qian, Ping
Abstract: Halide perovskite is a special kind of semiconductor, which is expected to apply in solar cells and electronic devices. A key characteristic of these materials is the carrier mobility, which determines the average electron velocity caused by the driving electric field. In the face of the complexity for experimental samples, it is very important to identify mobility's upper limit, and which parameters control it, so as to provide clear guidance for material application. In this study, the mobility for the tetragonal halide perovskite (CsSnCl 3, CsPbCl 3, CsSnBr 3 and CsPbBr 3 ) is predicted by semiempirical modes including both longitudinal acoustic (LA) and polar optical (PO) phonons. The results show that the mobility derived from LA phonon model is much higher than that from PO phonon model, so LA phonon is not the decisive scattering source. According to Matthiessen's rule, the carrier mobility for these perovskites is determined by PO phonon model. The electron and hole mobilities along [0 0 1] direction are about 52 and 133 cm 2 V − 1 s − 1 for CsSnCl 3, 35 and 33 cm 2 V − 1 s − 1 for CsPbCl 3, 94 and 198 cm 2 V − 1 s − 1 for CsSnBr 3, and 51 and 38 cm 2 V − 1 s − 1 for CsPbBr 3 . The mode analysis reveals that LO phonon associated with the fluctuations of divalent transition metal cations and halogen anions limits the mobility. This investigation provides some valuable information for the application of perovskite. Highlights: The mobility of tetragonal halide perovskite is predicted by LA and PO phonon models. The mobility from PO phonon model is much lower than that from by LA phonon model. Longitudinal optical phonon is revealed to be the main scattering source. Strong scattering comes from stretching of divalent metal cations and halogen anions. Electron cloud distortion and ion displacement under electric field limit the mobility.